Design and Development of an IoT-Based Room Cleaning Robot - Fahreza Yudhistira; A M H Pardede; Husnul Khair, (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
This research discusses the design and development of an Internet of Things (IoT) based room cleaning robot. The background of this research is based on the modern society's need for automated devices that can help maintain home cleanliness efficiently. The system is designed using the ESP32 as the main microcontroller, GP2Y1010AU0F dust sensor for dust detection, ultrasonic sensors for navigation, DC motors and L298N module for actuation, and Blynk application as a medium for remote control and monitoring. The testing results show that the robot can detect dust, perform simple navigation, activate the vacuum for cleaning, and send notifications to the Blynk application when the dustbin is full.